Evaluasi Ketersediaan Obat Di Puskesmas Pekauman Kota Banjarmasin Tahun 2021 - Mochammad Maulidie Alfiannor Saputera; Nida Hayati; Rina Feteriyani (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2023)
The availability of drugs at the Public Health Center Pekauman Banjarmasin, until December 2021, was only 69.86% conformity to drug acceptance with a total of 17,411 patient visits in 2021. This causes drug vacancies in the pharmacy room and pharmaceutical services to be less than optimal. The aim of the study was to find out the percentage of compliance with demand for drug acceptance and the level of drug availability at the Public Health Center in 2021. The sample in this study was the 2021 annual LPLPO using the Saturated Sampling method. The research instrument used an observation sheet with retrospective data collection. The results showed that the suitability of demand for drug acceptance at the Public Health Center was 68.46% and the level of drug availability in the Empty category was 244 drug items with a percentage of 55.70%, the drug availability rate in the safe category was 150 drug items with a percentage of 34.25%, The level of drug availability in the excess category was 44 drug items with a percentage of 10.05%. The average level of drug availability at the Public Health Center in 2021 is 8.71 months, which is in the less category.